Pyrroloindacenodithiophene containing polymers for organic field effect transistors and organic photovoltaics - Donaghey,JE; Ashraf,RS; Kim,Y; Huang,ZG; Nielsen,CB; Zhang,W; Schroeder,B; Grenier,CRG; Brown,CT; D'Angelo,P; Smith,J; Watkins,S; et al. (Journal of Materials Chemistry, 2011)
The synthesis of the novel electron-rich pyrroloindacenodithiophene (NIDT) unit is reported. Stille copolymerization of the distannylated NIDT unit, with the electron-deficient dibrominated benzothiadiazole (BT), difluorobenzothiadiazole (ffBT), thienopyrrolodione (TPD) and 1,1[prime or minute]-bithienopyrrolodione (biTPD) units afforded a series of low band gap semiconducting polymers. Initial testing shows promise for the use of these materials as p-type semiconductors in organic field effect transistors (OFETs) with mobilities as high as 0.07 cm2V-1s-1 being measured. These materials have also been tested as the donor polymer in polymer/fullerene bulk heterojunction organic photovoltaics (OPVs) giving maximum efficiencies of 2.5%.